Grooming as a Means to Cool Down - Maiden, Amy; Marshall, Jeremy L. (My University, 2017)
Many people believe that the only method of cooling down their horse is to walk them, and sometimes for long amounts of time depending on the work and length of work the horse was used for. Brushing a horse’s coat mimics a natural equine behavior (mutual grooming) between horses that can induce a horse to relax – and thus affect his heart rate and cause it to lower (EquiMed) quicker. There are even certain studies that show heart rate reduction when the withers and nearby areas were groomed, but no reduction when the shoulder and other areas of the horse was groomed (S. Normando). There is not a lot of research projects on this idea that heart rate could help cool down horses after a workout, which would in turn save some time for the horse’s caretaker. If a horse is groomed immediately following exertion, then their heart rate should decrease at a rate faster than if they were walked after the exerting exercise. I concluded that there is a faster decrease in heart rate of the horse following a few minutes of grooming. The results that were found here should help show and explain to horse owners that grooming is a good practice to exercise after a horse has exerted itself with work. This could be extremely beneficial to the racing industry, where the cool down process is extremely important but consumes large amounts of time.